The boundaries of education: using mobile devices for connecting people to places - David Lewis Sinfield (Association for Learning Technology, 2018)
This discussion paper explores pedagogy beyond the boundaries of tertiary institutional classrooms through a sociocultural lens that examines the history of a small-town community.In doing so, this paper discusses the principles informing the study and exploratory stages, and is not intended as an empirical research paper. Rather it outlines the use of mobile technologies to enhance the documentation of the sociocultural story of a community and as such presents a potentially transferable framework for utilising mobile mixed reality (MMR) to create authentic informal learning environments.This paper utilises (mobile) mixed media to document the historical, industrial and community growth and demise of a small town called Patea in Taranaki, New Zealand. Using practice-led methodology through a heuristic inquiry approach, the aim of the study is to demonstrate how MMR technology can be used to document the historical events and workers' narratives of the town and then be gifted back to the town as artistic educational material for future generations.As an example of a 'new genre of public art', this paper reflects on the collection of multiple forms of media capturing recorded interviews and the communication of the spoken word, mobile phone filming, drone footage, 360-degree photography/film, site recordings and the memories of what a place could be to create a new form of educational augmented reality/virtual reality (AR/VR) audio visual portraiture. The author argues that the use of MMR to form a collection of AR/VR short film poems creates powerful portraits of the people who worked in the now abandoned cool stores and freezing works at Patea.